2011
DOI: 10.4028/www.scientific.net/amr.255-260.1939
|View full text |Cite
|
Sign up to set email alerts
|

Structure Statics Finite Element Model Updating Based on Response Surface Methodology

Abstract: Employing response surface method, the complicated implicit relationship between bridge structural static-load responses and structural parameters is approximately represented by the simple explicit function. Based on this response surface model (function), the structural finite element model parameters can be easily updated by selected optimization procedure. By a numerical example of a two-span continuous beam, the essential theory and implementation of structural static response surface based finite element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…To cut down the cost, the response surface methodology is used in the optimization design. the detailed descriptions of the Response surface method can be found in research results [4][5][6].Generally, an objective function of design optimization can be formulated as follows [7]: Minimize:…”
Section: Mathematical Model Of the Methodsmentioning
confidence: 99%
“…To cut down the cost, the response surface methodology is used in the optimization design. the detailed descriptions of the Response surface method can be found in research results [4][5][6].Generally, an objective function of design optimization can be formulated as follows [7]: Minimize:…”
Section: Mathematical Model Of the Methodsmentioning
confidence: 99%
“…One possible way to improve computational efficiency is to use some machine learning methods in the process of model calibration. For example, Karimi et al [13] used the artificial neural network (ANN) and Deng et al [14] used the response surface model instead of the FEM to calculate the modal parameters of a structure during the optimizing search process. Response surfaces, ANN and some other traditional machine learning methods are based on the empirical risk minimization (ERM) [15], which requires a large amount of training samples and may cause an over-fitting problem.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive description of RSM theory can be found in [20]. Apart from chemistry and other realms of industry, RSM has also been introduced into the reliability analysis and model validation of mechanical and civil structures [21][22][23] and, moreover, it has been found to possess the capability of model updating [24][25][26]. By adopting the design of experiment (DOE) [27], RSM requires much lower training and construction efforts than the conventional FEMU-or NNbased methods.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness quantities and modal frequencies were used as input parameters and responses, respectively, and the authors found that, compared with the sensitivitybased FEMU, the RSM-based method gave likewise accurate predictions but was much more cost efficient than the former. Deng et al [25] utilized uniform design to generate an RS model for updating a numerical two-span continuous beam and it was observed that, compared with the conventional FEMUbased methods, the RSM-based method considerably improved updating efficiency without losing prediction accuracy. In another piece of research performed by Ren and Chen [26], the FD and the CCD with the modal frequencies as the responses were successfully applied to update a numerical beam and a tested full-scale box girder bridge, and similar conclusions as stated in [24] and [25] were found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation